PSYCHOANALYTIC ATTENDANCE IN SUBJECTIVE URGENCY : WOMEN IN SITUATIONS OF DOMESTIC VIOLENCE IN TIMES OF COVID-19 - Pinheiro Lopes, Janara; Mendes Tôrres Tomaz, Jerzuí; Maia Cruz, Danielle; Cavalcante Teixeira, Leônia; Andrade Braga Rocha, Bruna Estrela; José Barreira Danziato, Leonardo (Cadernos ESP, 2022)
The objective of this article is to analyze the apparatus of clinical-institutional listening in subjective urgency in public policy, with a focus on the psychoanalytic treatment of women (done remotely) in situations of domestic violence during the COVID-19 pandemic. The article discusses a paradigmatic clinical case, which is part of the intervention research project of the Laboratory of the Study of Psychoanalysis, Culture, and Subjectivity (LAEpCUS) at the University of Fortaleza (UNIFOR) in collaboration with the Nucleus for Confronting Violence Against Women (NUDEM), which is associated with the Public Defender of the State of Ceará. It problematizes the complexity of gender-based violence exhibiting the tensions within the vision of a victim/aggressor dichotomy. It concludes that against the backdrop of the coronavirus pandemic, new demands have been imposed on daily life, so that treatments of the mechanism of subjective urgency with women in situations of domestic violence, such as the one illustrated by the clinical case, permit a better positioning of them against their situations of vulnerability and risk. The interfaces between the judiciary and mental health point to successes in dealing with domestic violence